Application of Translation Workshop to College English Translation Teaching - Ge, Shan (International Journal of Emerging Trends in Social Sciences, 2021)
Undergraduate education throughout the world has long been confronted with the challenge of making students active learners who are responsible for their own learning. It has been widely recognized that higher education needs to turn to student-centered perspective and model which emphasizes students’ learning effect, or the outcomes of talent training. The traditional "teaching-centered" translation training mode adopted to teach non-English majors in Chinese universities cannot effectively improve students’ translation ability, though it may assist English language learning. The teaching mode of "translation workshop", aiming at improving students’ learning effect, emphasizes the learning process and enables students to learn and improve translation skills through real translation project, which is conducive to raising students’ awareness of cross cultural communication and cultivating their sense of responsibility as translators. The experiment done in the present study proves that applying "translation workshop" to teaching Chinese non-English majors can effectively stimulate students’ interest in learning, increase their participation in learning, and thus improve the effect of translation learning.